Experimental and theoretical investigation of the chemical exfoliation of Cr-based MAX phase particles. Issue 35 (13th July 2020) - Tran, Minh Hai; Malik, Ali M.; Dürrschnabel, Michael; Regoutz, Anna; Thakur, Pardeep; Lee, Tien-Lin; Perera, Delwin; Molina-Luna, Leopoldo; Albe, Karsten; Rohrer, Jochen; Birkel, Christina S.
Abstract : Experimental and theoretical evidence of the unexfoliability of Cr2 GaC MAX phase particles in aqueous hydrofluoric acid. Abstract : Two-dimensional carbides/nitrides, typically called MXenes, are an emerging member of the ever-growing family of two-dimensional materials. The prediction of a ferromagnetic groundstate in chromium-containing MXenes has triggered growing interest in their chemical exfoliation from Cr-based MAX phases. However, the exfoliation poses serious difficulties using standard etching agents such as hydrofluoric acid (HF). Here, we investigate the exfoliability of Cr2 GaC particles by chemical etching with aqueous HF both experimentally and theoretically. Structural and microstructural analyses show that the Cr2 GaC particles decompose into chromium carbide and oxide without the formation of a Cr-based MXene. A thermodynamic analysis based on ab initio electronic structure calculations reveals that the exfoliation of Cr-based MXene from Cr2 GaC by HF-etching is inhibited by more favorable competing reactions. This result confirms the experimental finding and suggests that HF is an unsuitable etching agent for a successful exfoliation of Cr2 GaC.